Seeing beyond the visible: how drones are revolutionizing rice farming in India and the Philippines - Gakhar, Shalini; Klassen, Steve (CGIAR Initiative on Digital Innovation, 2024)
The impact of drone technology is growing across various sectors, and agriculture is no exception.  Globally, the market for agricultural drones is worth US $32.4 billion, compared to US $127 billion for the total value of drone-powered solutions. For smallholder farmers in countries such as India and the Philippines, drones have the capability to function as an integrated solution for precision agriculture, enabling automated seeding, real-time crop health monitoring, precision spraying, and other critical farming operations. Their versatility lies in the multitude of sensors (Table 1) that can be mounted to gather information over large areas.